Safety evaluation of lactobacillus strains as potential probiotics for human use - Umar, Hadiza Meleh (2018)
Lactobacillus species are generally regarded as safe (GRAS) by the United State Food and Drug Administration (FDA) due to their long history of safe consumption in traditional fermented foods. However, there have been few reported cases of Lactobacillus species associated with clinical conditions such as bacteremia, endocarditis and localized infections. In view of this, it is relevant to have a more thorough safety assessment of new strains before use as probiotics. Therefore, the aim of this study was to evaluate the safety of a new potentially probiotic lactobacilli strains. In this study, safety assessment of five lactobacilli strains, previously characterized as potential probiotic bacteria was carried out to determine their suitability for human use. Antibiotic resistance patterns were determined using agar overlay disc diffusion method. Hemolytic activity, bile salt deconjugation and amino acid decarboxylase activity were determined in vitro on agar plates. Enzymatic activities and carbohydrate fermentation profile were determined using API systems. Bile salt hydrolase (BSH) activity and D-/L-lactic acid production were quantified spectrophotometrically. Among the five strains, Lactobacillus reuteri S29 PFB was evaluated for safety in vivo in a 28 day sub-acute oral toxicity study in 40 BALB/c mice. The mice were randomized into 4 groups and orally fed with L. reuteri S29 PFB (1 x 108, 109 and 1010 CFU/day). Blood and organs collected at the end of the intervention period were analyzed for health parameters (blood biochemistry, hematology and histopathology) and incidence of translocation to blood and organs. Results from this study demonstrated that all the strains were able to utilize glucose and lactose and the enzymatic profiles of the strains correlated with the carbohydrate fermentation. Harmful bacterial enzymes such as beta glucoronidase was not detected in all the strains. the tested lactobacilli strains were shown to be suceptible to penicillins, chloramphenicol and tetracycline. None of the strains were shown to be hemolytic or decarboxylate histidine, tyrosine, lysine or arginine to form biogenic amines. The concentrations of D-/L- lactic acid and bile salt hydrolase activity units were comparable to that of the commercial strain, L. reuteri RC-14. Results from the in vivo study demonstrated that oral administration of different doses of L. reuteri 29 PFB for 28 days had no adverse toxicological effect on the mice general health status, hematological and blood biochemical parameters and intestinal histological parameters. There were no incidence of translocation to blood and DNA fingerprinting patterns of isolates recovered from tissues did not match with that of the administered strain. Overall, the result from this study suggests that L. reuteri 29 PFB was shown to be a better candidate for probiotic development, and would likely be safe for human use.